METEOROLOGICAL OBSERVATIONS BY DATA-LOGGING AUTOMATIC WEATHER STATION AT DOME FUJI STATION - エノモト, ヒロユキ; モトヤマ, ヒデアキ; シライワ, タカユキ; サイトウ, タカシ; カメダ, タカオ; フルカワ, テルオ; タカハシ, シュウヘイ; ワタナベ, オキツグ; ENOMOTO, Hiroyuki; MOTOYAMA, Hideaki; SHIRAIWA, Takayuki; SAITO, Takashi; et al. (National Institute of Polar Research, 1996)
P(論文) Automatic weather stations (AWS) using data loggers were distributed along the traverse route from Syowa Station to Dome Fuji Station (3810m a. s. l.). A data logger was set at Dome Fuji Station in January, 1994 and the first year-round observations were performed at Dome Fuji Station. The temperature data shows recurring abrupt increases in winter. The minimum temperature in 1994 was -78.1℃ and the mean temperature was -52℃. Wind direction was highly variable. Katabatic wind with constant wind direction is not observed but wind direction rotated counter-clockwise throughout the year. There were some interruptions in the wind speed data, thus a complete wind speed data set could not be obtained at Dome Fuji Station. However, the data show a wind of 12.7m/s in winter. The wind direction in that case was between north and east. This could be a case of a storm at Dome Fuji Station. departmental bulletin paper